The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4028/www.scientific.net/amm.82.15
|View full text |Cite
|
Sign up to set email alerts
|

Urban Habitat Constructions under Catastrophic Events: The COST C26 Action

Abstract: The main objective of the international research project (COST C26 Action, Chairman F.M. Mazzolani) dealing with “Urban Habitat Constructions under Catastrophic Events” (2006 – 2010) was to increase the knowledge on the behaviour of constructions located in urban habitat and subjected to both natural and/or man-made catastrophic events, such as earthquakes, fire, wind storms, heavy snow loading, gas explosions, accidental impact from vehicles out of control and occasionally due to bomb blasts during terrorist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In comparison, tourists from neighbouring resort islands mainly go to Fenfushi to visit the Friday Mosque as part of a day excursion, since no tourist accommodation facilities are available on the island. While various studies have focused on geohazards in urban settlements (Borg et al, 2010;De Gregorio et al, 2010;Mazzolani et al, 2010;Narasimhan et al, 2010), the geographical setting of the islands in the Maldives, including Maamigili and Fenfushi, presents a significantly different scenario.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In comparison, tourists from neighbouring resort islands mainly go to Fenfushi to visit the Friday Mosque as part of a day excursion, since no tourist accommodation facilities are available on the island. While various studies have focused on geohazards in urban settlements (Borg et al, 2010;De Gregorio et al, 2010;Mazzolani et al, 2010;Narasimhan et al, 2010), the geographical setting of the islands in the Maldives, including Maamigili and Fenfushi, presents a significantly different scenario.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The reported casualties and damage due to construction infrastructures' failure urge for effective systems of repair and retrofitting to prevent the sudden occurrence of failure and progressive collapse. [1][2][3][4][5][6] In the USA, American Road and Transportation Builders Association (ARTBA) 7 has reported that more than 47,000 bridges in the country are structurally deficient and in urgent need to repair. Similarly, numerous damaged bridges in various places in the world have been reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…The approach of risk evaluation could be defined as the correlation and function of the identified hazards, according to the geographic and environmental specificities of heritage assets, and the detailed analysis of their vulnerability (building materials and building structure conservation state). (Stovel, H. 1998), (Accardo, G. et al, 2003), (Mazzolani, F., 2010).…”
Section: Motivationmentioning
confidence: 99%